Antecedents of Vaccine Hesitancy in WEIRD and East Asian Contexts - Courtney, Daniel S.; Bliuc, Ana-Maria (Frontiers in Psychology, 2021)
Following decreasing vaccination rates over the last two decades, understanding the roots of vaccine hesitancy has become a public health priority. Vaccine hesitancy is linked to scientifically unfounded fears around the MMR vaccine and autism which are often fuelled by misinformation spread on social media. To counteract the effects of misinformation about vaccines and in particular the falling vaccination rates, much research has focused on identifying the antecedents of vaccine hesitancy. As antecedents of vaccine hesitancy are contextually dependent, a one-size-fits-all approach is unlikely to be successful in non-WEIRD (Western, Educated, Industrialised, Rich, and Democratic) populations, and even in certain (non-typical) WEIRD sub-populations. Successful interventions to reduce vaccine hesitancy must be based on understanding of the specific context. To identify potential contextual differences in the antecedents of vaccine hesitancy, we review research from three non-WEIRD populations in East Asia, and three WEIRD sub-populations. We find that regardless of the context, mistrust seems to be the key factor leading to vaccine hesitancy. However, the object of mistrust varies across WEIRD and non-WEIRD populations, and across WEIRD subgroups suggesting that effective science communication must be mindful of these differences.